Description of some discursive strategies of advertisement slogans: An application of Charaudeau’s semiolinguistic theory - Othero, Gabriel de Ávila (2008)
This article focuses on the application of Charaudeau’s semiolinguistic theory in analyzing advertisement slogans. Based on concepts of Charaudeau (1983a) and (1983b), some Brazilian slogans are analyzed and debated. Furthermore, the original theory presented by Charaudeau is revisited and modified, in order to improve the analysis of the advertisement slogans. Key words: Semiolinguistcs. Semiolinguistc Analysis. Publicity Texts.